INVESTMENT IN PROMOTION OF AGRICULTURAL COMMERCIALISATION IN NORTHERN UGANDA - ONYIRU PRIMROSE (UCU, 2024)
This study details how investment can promote agricultural commercialization in Northern Uganda. This region has significant agricultural potential however due to adverse effects such as civil wars, climatic conditions and poverty, this potential has been eroded. The research examines the role of both public investment in terms of government intervention and private investments in terms of donor-funded initiatives which gear toward improving agricultural productivity and market access. Emphasis is placed on infrastructure development, credit finance and technological advancement as key areas where investment can promote agricultural commercialization. Through analysis of secondary data obtained from existing studies relating to this study, government reports, articles and websites, the study identifies existing gaps as well as opportunities which provide policy recommendations to attract and sustain investment. The findings show that there is potential for more investment to be made in order to transform agriculture from subsistence-oriented to market-oriented thereby boosting incomes and contributing to regional economic growth. This research offers relevant insights involving infrastructural development, credit finance and technological advancement to policy makers and potential investors in fostering sustainable agricultural commercialization in Northern Uganda.